2023
DOI: 10.1136/bmjopen-2022-066000
|View full text |Cite
|
Sign up to set email alerts
|

Group antenatal care compared with standard antenatal care for Somali-Swedish women: a historically controlled evaluation of the Hooyo Project

Abstract: ObjectivesComparing language-supported group antenatal care (gANC) and standard antenatal care (sANC) for Somali-born women in Sweden, measuring overall ratings of care and emotional well-being, and testing the feasibility of the outcome measures.DesignA quasi-experimental trial with one intervention and one historical control group, nested in an intervention development and feasibility study.SettingMidwifery-led antenatal care clinic in a mid-sized Swedish town.ParticipantsPregnant Somali-born women (<25 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…A Swedish project concluded that group antenatal care for women of Somali origin led to more comprehensive care as the voice and narratives of the women were strengthened and the midwives expanded their understanding of the women and their needs ( 61). An effectiveness evaluation indicated an improved understanding of health information; however, no effect was shown on postpartum depression (17). Further, a Swedish community-based bilingual doulas intervention indicated a potential to lower caesarean section/instrumental delivery, while no significant effect on postpartum depression was shown (18).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A Swedish project concluded that group antenatal care for women of Somali origin led to more comprehensive care as the voice and narratives of the women were strengthened and the midwives expanded their understanding of the women and their needs ( 61). An effectiveness evaluation indicated an improved understanding of health information; however, no effect was shown on postpartum depression (17). Further, a Swedish community-based bilingual doulas intervention indicated a potential to lower caesarean section/instrumental delivery, while no significant effect on postpartum depression was shown (18).…”
Section: Discussionmentioning
confidence: 96%
“…There is a need to learn across the interventions, develop new clinical outcome measures, and have more consistency in the choice of outcomes, which can reflect improved communication and interactional dynamics of importance to maternal and perinatal health and morbidity. The MAMAACT study is the largest of the mentioned trials in the field (17,18,22), involving almost all maternity wards in Denmark, and the only one designed as a cluster-randomised trial. The limitations of the different data sources and specific analytical approaches are in detailed discussed in the original articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formative evaluation report is also available via the study website [30]. GPC for women of refugee background is the first model of its kind in Australia and one of the first worldwide [31]. In the context of the unique nature of this model and the small staff teams at each site, and to prevent participant identities from being deduced by local readers of this paper, we use the language 'professional staff' to refer to the range of clinical and social care staff, stakeholders, and leaders involved in the implementation, facilitation, or oversight of GPC for women of refugee background.…”
Section: Research Aimsmentioning
confidence: 99%